(untitled) (Intent Research Scientific Journal, 2024)
The findings in this article underscore the importance of studying linguistic expressions of cultural concepts to foster cross-cultural understanding. They also highlight how language evolves to reflect contemporary challenges, such as globalization and shifting societal priorities, while retaining its historical essence.